Sex-Role Identification and Violent Victimization: Gender Differences in the Role of Masculinity. (January 2014) - Daigle, Leah E.; Mummert, Sadie J.
Although sex-role identification has been found to be associated with crime and delinquency, the link between sex-role identification and violent victimization has remained largely unexplored. Using the Add Health data, this study examines sex-role identification and its relationship to violent victimization. The findings suggest that masculinity increases the risk of violent victimization for males, but does not for females. Other differences in risk factors across gender were also found. These findings indicate that masculinity is an important construct in understanding the complexity of why some persons are violently victimized and others are not.